2021
DOI: 10.1186/s10194-021-01359-8
|View full text |Cite
|
Sign up to set email alerts
|

Src family kinases activity is required for transmitting purinergic P2X7 receptor signaling in cortical spreading depression and neuroinflammation

Abstract: Background Purinergic P2X7 receptor plays an important role in migraine pathophysiology. Yet precise molecular mechanism underlying P2X7R signaling in migraine remains unclear. This study explores the hypothesis that P2X7 receptor transmits signaling to Src family kinases (SFKs) during cortical spreading depression (CSD) and neuroinflammation after CSD. Methods CSD was recorded using electrophysiology in rats and intrinsic optical imaging in mouse … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Both ATP and glutamate are bound by P2X7 receptors. In cultured and in situ astrocytes, activating these receptors causes ATP uptake and glutamate release at the same time [ 215 ]. Radiolabeled tracers were used to establish the release of L-glutamate and D-aspartate through P2X7 channels [ 214 ].…”
Section: Major Participants In Astrocytic Glutamatergic Transmission ...mentioning
confidence: 99%
“…Both ATP and glutamate are bound by P2X7 receptors. In cultured and in situ astrocytes, activating these receptors causes ATP uptake and glutamate release at the same time [ 215 ]. Radiolabeled tracers were used to establish the release of L-glutamate and D-aspartate through P2X7 channels [ 214 ].…”
Section: Major Participants In Astrocytic Glutamatergic Transmission ...mentioning
confidence: 99%
“…Nevertheless, regardless of how the P2X7R contributes to AD, these results strongly suggest that P2X7R is involved in memory loss and, consequently, identify the P2X7R as a possible therapeutic target to counteract cognitive decline seen, for example, in epilepsy [188]. Migraine is another common CNS disease associated with epilepsy, where P2X7R activation has been suggested to contribute to the pathology of the disease [189]. Cardiovascular conditions are among non-CNS diseases associated with epilepsy where P2X7R activation has also been suggested as a contributor.…”
Section: P2x7rs and Other Common Co-morbidities Associated With Epilepsymentioning
confidence: 97%
“…Subtle, but noteworthy, differences may exist in the occurrence and development of different NDs. Studies have shown that P2 × 7R/SFK signaling may be involved in the pathophysiology of cortical-spreading-depression-associated migraine [ 45 ].…”
Section: Electrophysiology and Related Signaling Pathways Of P2 × 7rmentioning
confidence: 99%